2006
DOI: 10.1002/adma.200502200
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Induced Ferromagnetism in Co‐doped ZnO

Abstract: Dilute magnetic semiconductors (DMSs) that are formed by the partial replacement of cations in semiconductors by magnetic transition metal ions have drawn considerable attention because of their potential use in spintronic devices. [1,2] Many reports on the observation of ferromagnetism (FM) at room temperature in transition-metal-doped ZnO, TiO 2 , and other semiconducting oxides have been published.[3±14] However, the origin of FM in these materials is still not well understood. Mechanisms based on carrier-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
141
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(154 citation statements)
references
References 28 publications
12
141
1
Order By: Relevance
“…We show that samples lose their magnetism after the number of oxygen vacancies are reduced by annealing in air and this occurs even when the samples still show metallic conductivity due to ionized donors. This contrast with earlier studies in which both the magnetism and the metallic conductivity vanished after annealing in air 27,28 .These findings help to enrich our understanding of the microscopic origin of ferromagnetism 5 in oxides DMSs.…”
Section: Introductioncontrasting
confidence: 55%
“…We show that samples lose their magnetism after the number of oxygen vacancies are reduced by annealing in air and this occurs even when the samples still show metallic conductivity due to ionized donors. This contrast with earlier studies in which both the magnetism and the metallic conductivity vanished after annealing in air 27,28 .These findings help to enrich our understanding of the microscopic origin of ferromagnetism 5 in oxides DMSs.…”
Section: Introductioncontrasting
confidence: 55%
“…For instance, it has been shown that the ferromagnetism of both epitaxial 4,12 and nanoparticle thin films 13,4 of Co:ZnO can be reinforced by exposing them to Zn vapor, which was recently shown to generate zinc interstitials ͑Zn i ͒ n-type defects. 14 On the other hand, fast annealings of Mn:ZnO nanocrystals capped with N-rich molecules 4 have been shown to enhance their ferromagnetism.…”
Section: Introductionmentioning
confidence: 99%
“…In these n-type samples, the magnetization decreases sharply as oxygen is added. 4,[8][9][10] An undoped ZnO film has Zn interstitials and O vacancies when oxygen deficient and Zn vacancies and O interstitials when grown with excess oxygen. The magnetism in the films with excess oxygen is due to Zn vacancies.…”
mentioning
confidence: 99%
“…These include the stoichiometric transfer of material from the target to the film and the control of oxygenation during the film growth. A general trend for Co-doped ZnO has been to find that a deficiency of oxygen in the growth chamber enhances the ferromagnetism through the formation of donor states [4][5][6][7] and that annealing films in air or oxygen quenches any magnetization [8][9][10] although there are also a few conflicting results in which magnetism is observed in ZnO oxygenated films with and without doping with Co. 11,12 The role of metallic Co precipitates is less clear, with some authors claiming that they are responsible for all of the observed magnetic properties [13][14][15] ; however, other authors have identified ferromagnetic phases in ZnCoO films that lack any metallic component. 16,17 The PLD growth of ZnCoO starts from a target that has been made to the desired composition by a solid-state reaction of a Co-containing compound and zinc oxide.…”
mentioning
confidence: 99%